Effects of lime and phosphate on mungbean and groundnut in irrigated acid sulphate soils - Gautam, Anand Kumar; Hansen, Gunner K.; Tinsley, Richard L.; Salokhe, Vilas M.; Boonjit Titapiwatanakun; United States Agency for International Development (USAID); CHEMONICS International (Bangkok : Asian Institute of Technology, 1996)
A field experiment was conducted on irrigated acid sulphate soil (Sulfic tropaquept) of Bangkok Plain at Asian Institute of Technology during the dry season of 1996 in order to investigate the effect of lime and phosphorous on soil pH and on growth, yield, nutrient concentration of mungbean (Vigna radiata L. WilczeK) and Groundnut (Arachis hypogea L.) and to simulate groundnut yield using PNGROW model and together with CERES-rice model analyze possible double cropping pattern. The experiment was laid out in split plot design with three replications with three levels of lime (0, 5 and 10 t ha-1) as main plots and three levels of phosphorous (0, 50 and 100 kg P2O5 ha-1) as sub plots. In soil, application of lime significantly increased pH. Liming increased exchangeable Ca and Mg in soil. Soil pH, available P and exchangeable Ca and Mg of underneath layer were not influenced by liming at upper layer. Bray II P increased with added lime and phosphorous at the zone of incorporation. Liming significantly increased the plant height, rooting depth, pods per plant, seed yield and total dry matter yield of mungbean. Lime had non-significant effect on plant height and seed yield of groundnut. Ca concentration was significantly higher in the seeds of both crops in the limed plots than unlimed plots. Application of phosphorous increased the plant height, seed yield and total dry matter yield of mungbean reflecting to be limiting nutrient. Its effect was non-significant to groundnut seed yield. Significant higher P concentration in straw and seeds of both crops and total P uptake was observed due to phosphorous application. A second-order polynomial regression revealed positive relationship between total N, P and K uptake and total dry matter (straw and seed) yield of both crops. The relationship between total Ca and Mg uptake and total dry matter yield was more pronounced in mungbean. Comparing to these two crops, total nutrients uptake were more limit in mungbean than in groundnut. In economic term, control treatment (L0P 0) required lowest variable cost in both crops. First level of phosphorous in mungbean and second level in groundnut without lime gave highest net returns. Marginal rate of net return in both crops were highest in the treatment with first level of phosphorous without lime. Compared to groundnut, mungbean gave higher marginal rate of net return in this treatment combination. No differences were found in between simulated and experimental results in seed yield, flowering and maturity days, nitrogen concentration in seeds and straw of groundnut. The model PNGROW and CERES-rice used in optimization of planting date in a irrigated double cropping system of rice and groundnut showed high degree of reliability.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1996
Keywords: Liming of soils; Mung bean -- Soils; Peanuts -- Soils